The public space in bogotá (1990-2006) (2007)
This article offers a review of the bibliography written during the period 1990-2006 about the public space in Bogotá. Following the main themes and focuses characterizing that bibliography, the author evaluates the knowledge about the urban public space produced by the Social Sciences. Also, the article highlights the relationships between those studies and the public space policy in Bogotá.